Using the iSpring Suite computer platform in distance learning - Kirillov Yuri (SHS Web of Conferences, 2021)
The article discusses the experience of using the iSpring Suite 9 computer platform as an information tool for conducting distance classes with second-year students in the training for “Business Informatics”. Self-isolation requirements in the face of the COVID-19 pandemic have required the development and use of innovative remote learning methods. The need to conduct practical classes on solving technical problems with mandatory time control and prompt receipt of the results of the solution by the teacher determined the requirements for the choice of a computer program as a tool for providing distance work in the field of education. As a result, the choice was made in favor of the corporate training platform iSpring. According to the results of the spring semester, the experience of working with iSpring Suite 9 in creating electronic tests and conducting practical exercises in distance mode was recognized as successful and will be used in the future to conduct classes with students of the distance department of Novosibirsk State Technical University.